2022
DOI: 10.7759/cureus.31244
|View full text |Cite
|
Sign up to set email alerts
|

Primary Hyperparathyroidism: Is Image Localization Alone Sufficient to Ensure Long-Term Cure in Unifocal Disease?

Abstract: Introduction: Advances in imaging have facilitated precise preoperative localization and focused resection of hyperfunctional parathyroids in primary hyperparathyroidism (PHPT). Combining imaging techniques or a "dual" approach, when concordant, improves adenoma-localizing accuracy above individual modalities. This study sought to assess biochemical cure and failure rates (persistence or recurrence) of surgery directed by dual imaging alone in PHPT.Methodology: This observational, single-center analysis compri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Some even suggested that 11 C‐methionine PET/CT is the preferable imaging modality over 99m Tc‐MIBI 18,24,27 . It is reported that concomitant thyroid disease may contribute to discordant US and 99m Tc‐MIBI results, and be a risk factor for surgical failure 39 . Eleven patients in our cohort had coexisting thyroid pathology and in seven patients (63.6%) 11 C‐methionine PET/CT correctly identified the adenoma.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Some even suggested that 11 C‐methionine PET/CT is the preferable imaging modality over 99m Tc‐MIBI 18,24,27 . It is reported that concomitant thyroid disease may contribute to discordant US and 99m Tc‐MIBI results, and be a risk factor for surgical failure 39 . Eleven patients in our cohort had coexisting thyroid pathology and in seven patients (63.6%) 11 C‐methionine PET/CT correctly identified the adenoma.…”
Section: Discussionmentioning
confidence: 72%
“…18,24,27 It is reported that concomitant thyroid disease may contribute to discordant US and 99m Tc-MIBI results, and be a risk factor for surgical failure. 39 Eleven patients in our cohort had coexisting thyroid pathology and in seven patients (63.6%) 11 C-methionine PET/CT correctly identified the adenoma. No difference in prevalence of coexisting thyroid disease was observed between the patients that did and that did not localise on 11 Cmethionine PET/CT.…”
Section: Sensitivitymentioning
confidence: 71%